Caracterização físico-química do fruto e micropropagação do maracujá-do-sono (Passiflora setacea DC.) - Santos, Flávia Carvalho (2006)
In function of the propagation difficulty of the Passiflora setacea DC., in seed germination, as well as in the rooting of cuttings, tissue culture techniques become viable for its propagation. The object was to obtain in vitro germination and to determine the culture medium for the in vitro micropropagation of Passiflora setacea DC. The experiments were carried out in the Tissue Culture Laboratory of the Department of Agriculture in the Federal University of Lavras. Physical-chemical analysis of Passiflora setacea DC. fruits from the EMBRAPA Cerrados Research Center, Planaltina, DF, were done. The results presented the following characteristics: length-5.38 cm, diameter-4.30 cm, fruit weight-47.26 g (21.94 g of peel and 25.32 g of pulp + peel), average pulp yield-53.6%, seeds per fruit-205, juice acidity level-2,61%, Brix scale level-16.8 and pH-3.04. Seeds originating from this analysis were used in the dormancy break experiment which consisted of the following treatment: doses of gibberellic acid (0; 20; 40 mg.L-1), combined with scarification presence (cut on the tip of the seed, in the middle and absence). It was observed that the use of 20 mg.L-1 of GA3 and scarring the tip of the seeds (close to the embryo) provided a higher dormancy percentage and germination speed index. Plantlets originating from of the in vitro germination experiment were used for the germination experiment. The tested culture mediums were, MS, MSM, BDS, DSD1and WPM combined with sucrose concentrations (0, 15, 30, and 45g.L-1). The use of the MSM culture medium associated with 28.51 and 28.74 g.L-1 of sucrose promoted larger length of the aerial part and number of buds, respectively. The medium MSM supplemented with 45 g. Sucrose L-1 provided higher dry matter weight of the plantlets. There was no root or shoot presence in any of the treatments of the assay.